Heatlines visualisation of mixed convection flow in a wavy heated cavity filled with nanofluids and having an inner solid block. (1st June 2020) - Azizul, Fatin M.; Alsabery, Ammar I.; Hashim, Ishak
Highlights: Mixed convection and heatlines visualization of nanofluid in wavy enclosures including inner solid block is determined. Finite element method was employed to solve the dimensionless governing equations in 2D weak formulations. Comparisons among experimental/numerical data are accomplished concerning the validity of the existing code. Impacts of number of oscillation and inner block length on the rate of heat transfer are established. Graphical abstract: Abstract: In the present numerical work, the visualisation of heatlines on nanofluids mixed convection flow in a wavy bottom cavity, including a solid inner body are reported. Using the finite-element technique, the dimensionless governing equations are solved subjected to specific boundary conditions. Comparisons with the experimental/numerical data are accomplished regarding the validity of the existing code. The numerical results are explained in the form of streamline, isotherms and heatlines structures as well as heat transfer characteristics with variations of the Reynolds number, Grashof number, nanoparticles volume fraction, fraction of undulations and dimensionless length of the inner solid block. It has been found that the high value of Reynolds number gives a better fluid flow and a reasonable rate of convective heat transfer. It has been confirmed that within the convection mechanism, for a high Grahsof number natural convection dominates, which achieves the maximum rate of heat transfer in the system. Also, the size of the internal object minimizes the space inside the wavy cavity and it was found that D = 0.3 is the perfect size located within the centre of the cavity.